Effect of Resident Participation on Outcomes in High-Order Cesarean Deliveries. (October 2015) - Mourad, Mirella; Gupta, Simi; Rebarber, Andrei; Saltzman, Daniel H.; Fox, Nathan S.
Abstract : OBJECTIVE: To estimate the effect of resident participation on outcomes in women undergoing high-order cesarean deliveries. METHODS: We performed a retrospective cohort study of patients in one obstetric practice undergoing a third- or greater order cesarean delivery from 2005 to 2014. Patients with placenta previa, accreta, or failed vaginal birth after cesarean delivery were excluded. We compared outcomes between patients whose operations were performed by two attendings with patients whose operations were performed by one attending and one resident. Regression analysis was performed to control for differences at baseline. RESULTS: Three hundred seventy patients were included, 189 (51%) of whom had two attendings and 181 (49%) of whom had one attending and one resident. The mean operative time was slightly but significantly less in the two=attending group (60.9±17.3 compared with 62.5±18.3 minutes, adjusted P =.038). Otherwise, there were no significant differences in measured outcomes between the groups, including wound complications, blood loss (estimated and drop in hemoglobin), blood transfusion, major maternal morbidity (hysterectomy, cystotomy, bowel injury, intensive care unit admission, thrombosis, reoperation, death), postoperative endometritis, and postoperative days in the hospital. Among patients in the resident group, there was no difference in outcomes between cases performed by a junior (first or second year) resident compared with a senior (third or fourth year) resident. CONCLUSION: Resident participation does not negatively affect outcomes in patients undergoing high-order cesarean deliveries. Residents should be included in these complicated cases because they can obtain a significant learning experience without compromising patient safety. Abstract : Resident participation does not negatively affect outcomes in patients undergoing high-order cesarean deliveries.